The Implementation of the LAMIKRO Application to Improve the Accuracy of Financial Recording and MSME Compliance Based on SAK EMKM at Grosir Karya Muda - Ihsan, Khairil; Syafina, Laylan; Nasution, Yenni Samri Juliati (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the implementation of the LAMIKRO application in improving the accuracy of financial record-keeping and compliance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) among MSMEs, with a particular focus on Grosir Karya Muda. MSMEs play a strategic role in Indonesia's economy but often face challenges in effective financial management due to limited accounting literacy and resources. LAMIKRO, an Android-based application, offers a solution through features such as journal entries, income statements, and balance sheets to facilitate the preparation of financial reports in accordance with SAK EMKM This study employs a descriptive qualitative method using primary data obtained through interviews, observations, and documentation. The findings reveal that the use of LAMIKRO significantly enhances the accuracy of financial record-keeping and the quality of MSME financial reports. Furthermore, intensive assistance in using the application helps overcome barriers related to digital literacy and the lack of prior outreach, which were previously major obstacles. Thus, LAMIKRO not only improves financial management efficiency but also strengthens the credibility of MSMEs in accessing financing.